Fulfilling the Rights of Social Workers: Aspects of Social Security in Indonesia - Utang Rosidin; Ardika Nurfurkon; Dedy Pribadi Uang (Khazanah Hukum, 2024)
The purpose of this article is to describe the fulfillment of social work rights, analyzing the extent to which the government provides social security for social workers. This study uses a qualitative method with a normative juridical approach. The analysis in this study contributes to the fulfillment of social workers' rights in terms of social security and provides recommendations regarding social security regulations as a fulfillment of social workers' rights. The results show that three aspects must be considered in the rights of social workers to social security in Indonesia, namely (1) Fulfillment of Social Workers' Rights, (2) Anticipation of regulations against the risks of social workers, and (3) Social security for social workers in Indonesia. From these three aspects, there are several efforts made by the government in regulation that has issued Law Number 14 of 2019 concerning Social Workers, but the law only regulates the Rights and Obligations of Social Workers in Indonesia. The findings may also impact the lives of social workers, including improved financial well-being, job security, and professional satisfaction. Previous studies have not discussed the aspect of social security as a fulfillment of social workers' rights, so this research contributes to this void by paying attention to the analysis of the fulfillment of social workers' rights in terms of social security aspects.